Dhikr as an Effort to Increase Learning Motivation of Grade XII Students at MAS Al-Amanah Al-Gontory - Arif Suci Kurniasihanto; Selvy Yuspitasari; Riyan Hidayatulloh (Cv. Kayaswara, Indonesia, 2025)
This study aims to explore the impact of Dhikr Asmaul Husna on enhancing learning motivation among students at MAS Al-Amanah Al-Gontory. The research employs a qualitative approach, utilizing purposive sampling and snowball sampling techniques to gather data from a range of students and teachers. Data was collected through interviews, observations, and documentation. The findings reveal that the regular practice of Dhikr Asmaul Husna, conducted each morning before lessons, significantly enhances students’ motivation to learn. The practice fosters a closer connection with Allah SWT, promoting inner peace and focus, which positively impacts their academic engagement and performance. Both intrinsic and extrinsic motivations play a role in students' learning behaviors, with dhikr strengthening their intrinsic motivation while external rewards such as grades serve as extrinsic motivation. The study suggests that incorporating spiritual practices in educational settings can be an effective method for improving student motivation. Future research could examine the long-term effects of such practices and compare them with other spiritual or educational interventions.